Aperiodic exchange modulation effect on the specific heat in the Kondo necklace model - Reyes D. (2019)
D. R. would like to thank the Condensed Matter Research Group of San Marcos University, where part of this work was performed. G. C. -S., H. S. T., and R. M. E. -B. are grateful to National Council of Science and Technology (CONCYTEC) from Peru for the financial support through the Doctoral Program for Peruvian Universities (Nro 218–2014-CONCYTEC). C. V. L. and D. R. are grateful to the Programa Nacional de Innovación para la Competitividad y Productividad of the Peruvian Agency Innovate Perú for financial support under contract number Nro. 457-PNICP-ECIP-2015. C. V. L. would also like to thanks the San Marcos University for partial financial support under project number B17130021.